2019
DOI: 10.25077/jfu.8.1.57-63.2019
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Nilai Noise dari Citra Pesawat CT-Scan pada Beberapa Rekonstruksi Kernel dengan Variasi Slice Thickness

Abstract: Telah dilakukan penelitian tentang analisis nilai noise dari citra pesawat CT-Scan pada beberaparekonstruksi kernel dengan variasi slice thickness. Penelitian dilakukan dengan menggunakan fantom sebagai bahan pengganti pasien. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan rekonstruksi kernel terhadap nilai noise. Nilai noise ysng didapatkan dibandingkan dengan batas toleransi yang diizinkan oleh BAPETEN. Slice thickness terbaik akan ditentukan dari masing-masing rekonstruksi yang digunakan. Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
1
Order By: Relevance
“…(Kofler et al, 2015) Parameter lain yang mempengaruhi kualitas citra CT scan yaitu ketebalan slice thickness Slice thickness adalah tebalnya irisan atau potongan dari objek yang diperiksa. (Hutami et al, 2021), (Bisra, 2020), (Almuslimiati et al, 2019) Umumnya ukuran yang tebal akan menghasilkan gambaran dengan detail yang rendah dan dosis radiasi yang rendah. (Nurhayati et al, 2019) Pemilihan Slice Thickness yang tepat dapat menegakkan diagnosa dengan baik.…”
Section: Pendahuluanunclassified
“…(Kofler et al, 2015) Parameter lain yang mempengaruhi kualitas citra CT scan yaitu ketebalan slice thickness Slice thickness adalah tebalnya irisan atau potongan dari objek yang diperiksa. (Hutami et al, 2021), (Bisra, 2020), (Almuslimiati et al, 2019) Umumnya ukuran yang tebal akan menghasilkan gambaran dengan detail yang rendah dan dosis radiasi yang rendah. (Nurhayati et al, 2019) Pemilihan Slice Thickness yang tepat dapat menegakkan diagnosa dengan baik.…”
Section: Pendahuluanunclassified
“…It was concluded that the noise values obtained for all the reconstruction kernels used were within tolerance limits, and there was an impact of slice thickness. In 2020 [1], Putra Doharmansyah evaluated noise with exposure variation using the NPS method. The study found that exposure variation had an impact on the CT Scan system, and the NPS method was found to be a good approach [13].…”
Section: Introduction 1*mentioning
confidence: 99%
“…However, the risk of error and calibration system failure of the x-ray generating system in the x-ray tube could have happened. It can affect the image quality and the dose of P-ISSN : 2615 -1278, E-ISSN : 2614 -7904 radiation X-rays given to the patient [3]. Therefore, it is necessary to carry out Quality Control (QC) of the CT-Scan to ensure the best image quality and keep the radiation dose for patient safety within the given tolerance limits [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Phantom is used to calibrate imaging systems, evaluate CT performance, and ensure the correct operation of imaging systems before scanning humans or an object. The component of this phantom is water because that makes the soft tissues in the human body, which is about 90% [3]. So that measurements during testing can be carried out repeatedly and the results are more accurate.…”
Section: Introductionmentioning
confidence: 99%